2008
DOI: 10.1071/rd08004
|View full text |Cite
|
Sign up to set email alerts
|

Expression and compartmentalisation of the glycolytic enzymes GAPDH and pyruvate kinase in boar spermatogenesis

Abstract: Boar spermatozoa contain isoforms of both glyceraldehyde 3-phosphate dehydrogenase (GAPDH, EC 1.2.1.12) and pyruvate kinase (PK, EC 2.7.1.40). The sperm-specific forms, GAPDH-S and PK-S, are tightly bound to cell structures. By immunofluorescence microscopy GAPDH-S and PK-S were localised in the principal piece of the boar sperm flagellum as well as in the acrosomal region of the sperm head and at the head-midpiece junction. The midpiece of the flagellum, however, contains isoforms of GAPDH and PK that were on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Surprisingly, some of them, aldolase A (ALDOA) and triosephosphate isomerase (TPI1), have been proposed to mediate interactions with ZP glycoproteins . Our data also affirmed the presence of metabolic enzymes such as hexokinase‐1 (HK1) , glyceraldehydes‐3‐phosphate dehydrogenase (GAPDHS) pyruvate kinase (PK) , and enolase‐1 (ENO1) . These proteins have been found in posterior and anterior regions of the sperm head in murines and boar, ENO1 in human sperm.…”
Section: Discussionsupporting
confidence: 69%
“…Surprisingly, some of them, aldolase A (ALDOA) and triosephosphate isomerase (TPI1), have been proposed to mediate interactions with ZP glycoproteins . Our data also affirmed the presence of metabolic enzymes such as hexokinase‐1 (HK1) , glyceraldehydes‐3‐phosphate dehydrogenase (GAPDHS) pyruvate kinase (PK) , and enolase‐1 (ENO1) . These proteins have been found in posterior and anterior regions of the sperm head in murines and boar, ENO1 in human sperm.…”
Section: Discussionsupporting
confidence: 69%
“…Spot 10Fl was identified as Glyceraldehyde 3-phosphate dehydrogenase (GAPDH). This protein is expressed in sperm at specific stages of spermiogenesis and can still be detected in mature spermatozoa of vertebrates [43]. Variations in the expression of GAPDH block the progressive motility of spermatozoa [44].…”
Section: Discussionmentioning
confidence: 99%
“…For the rabbit muscle, it was demonstrated that this enzyme dissociates into inactive subunits under acidic conditions and re-associates into the active form when the pH is raised again [6], [7], [36]. In quiescent epididymal mouse spermatozoa hexokinase activity was significantly lower compared to that of sperm incubated in physiological buffer [36].…”
Section: Discussionmentioning
confidence: 99%
“…Besides mitochondrial respiration, glycolysis is a major pathway for ATP production in murine spermatozoa [2], [3], [4]. Glycolytic enzymes are located in the fibrous sheath of the sperm tail [5] and some of them exhibit sperm-specific properties, such as type1 hexokinase (HK1S) [6], pyruvate kinase (PKS) [7] and glyceraldehyde 3-phosphate dehydrogenase (GAPDS) [8]. The fibrous sheath covers the outer dense fibers which, in turn, are located in close proximity to the microtubules.…”
Section: Introductionmentioning
confidence: 99%